Tema dan Pola Penggambaran Suasana pada Alih Wahana Puisi di Youtube - Fildzah Rahmatina; Muhamad Haryanto (Jurnal Bahasa dan Sastra, 2022)
The presence of YouTube poetry has resulted in the emergence of many new poets and the increasing development of the world of literature. The purpose of this research to describe the tendency of the theme and depiction of the scene in the poetry ecranisation on Youtube. The research method used is a qualitative quantitative method with statistical analysis. Data collection techniques in this study used observation and documentation techniques. Data analysis in this study included grouping data based on variables and types of respondents, tabulating data based on variables, presenting data on each variable studied, performing calculations to answer the problem formulation and testing hypotheses. The results of research about theme of poetry ecranisation on Youtube tend be themed about love, such as appiness because of love, disappointment because of love, sadness because of love, lost because of love. The themes show 77% about sadness and 23% about happiness. The theme is contained in several accounts, namely Fiersa Besari. Boy Candra, Catatan Khoirul Trian, Salshabilla TV, Wira Nagara, Rhia Lestari, Fiksionalisme, Pena Safa, MIHP, Ika Nacita, dan Bedcover Official. The depiction of the scece in the poetry ecranisation on Youtube tends to display images as a support the scene, cinematic videos, and simple videos.